The Environmental Kuznets Curve Hypothesis: an Empirical Evidence in Indonesia - Setiawan, Avi Budi; Anwar, Mochamad Syaiful (Universitas Negeri Semarang, 2022)
The Environmental Kuznets Curve (EKC) hypothesis is the relationship between environmental and economic indicators forming an inverted U-curve. This paper aims to provide new insights using the long-term Vector Error Correction Model (VECM) technique. The research data use time series from 1974 to 2020. Empirical findings result in the formation of an open U-curve phenomenon. The immature post-industrialization stage in Indonesia hurts increasing CO2 emissions. Economic indicators as control variables that include population, consumption of electrical energy, and international trade ratios have a good impact on reducing CO2 emissions. The indicator of fossil energy consumption shows that Indonesia still has a dependence on non-renewable energy. After the ratification of the Kyoto Protocol in Indonesia, it does not have promising implications for reducing CO2 emissions. This paper provides important implications for establishing strict regulations to reduce CO2 emissions that contribute to climate change. In the future, the government must encourage people's behavior to save energy, optimize renewable energy, change energy demand patterns, transform low-carbon export products, and evaluate international agreements that impact the pattern of sustainable development in Indonesia.